Different Avenues of Capital Market (Secondary Market) Available for Investing in Market of Yamuna Nagar - Aggarwal, Rajat (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
Within the financial sector, the term "financial markets" is often used to refer just to the markets that are used to raise finance: for long term finance, the Capital markets; for short term finance, the Money markets. Capital markets which to consist of...